THE ROLE OF OMEGA-3 FATTY ACIDS IN SLEEP DEPRIVATION AND MENTAL HEALT: A NARRATIVE REVIEW - Galińska, Dominika; Domańska, Natalia; Roman, Anna; Zajączkowska, Joanna; Marzec, Natalia; Krupa, Natalia; Marzec, Aleksandra; Cherek, Małgorzata; Praska, Weronika; Wardęcki, Stanisław Maria (International Journal of Innovative Technologies in Social Science, 2026)
Objectives: The influence of omega-3 fatty acids on sleep disorders and mental health functio-ning constitutes a complex research problem, necessitating a clear distinction between their the-rapeutic potential and alleged prophylactic properties. Unrecognized neurochemical imbalances and neuroinflammatory states may contribute to the development of depression, anxiety, and insomnia, making a rigorous assessment of supplementation efficacy essential for safe and accu-rate therapeutic decisions. Our objective is to present a comprehensive synthesis of current evi-dence regarding the mechanisms of action, clinical effectiveness, and limitations of omega-3 fatty acid use in the context of sleep quality and mental health.Methods: Based on the available sources, a narrative literature review was conducted, focusing on studies analyzing the influence of polyunsaturated fatty acids (primarily EPA and DHA) on the nervous system. The evidence was synthesized based on observational and experimental studies, meta-analyses of randomized clinical trials, and current clinical guidelines (including those regarding the use of nutraceuticals in the treatment of psychiatric disorders).Key findings: Omega-3 fatty acids, specifically DHA and EPA, constitute key modulators of cell membrane structure, neurotransmission (dopaminergic and serotonergic systems), and the melatonin secretion rhythm. Current evidence strongly supports their use as adjunctive therapy in the treatment of depressive disorders and the alleviation of anxiety, particularly in patients with elevated inflammation and oxidative stress. However, they are not recommended as mo-notherapy. There is also a lack of evidence confirming their efficacy in the primary prevention of depression in healthy individuals. Accumulated data indicate that improvement in objective sleep parameters and mood stabilization require an individualized approach, and the therapeutic effect depends largely on the patient's baseline metabolic status.Conclusion: Omega-3 fatty acids may perform a significant corrective and supportive function in the treatment of mental disorders and sleep problems, acting as a stabilizer of pathological neurobiological changes rather than a universal mood enhancer. Integrated with appropriate cli-nical diagnostics, they allow for the safe support of standard pharmacotherapy. Future research should focus on determining optimal doses and EPA/DHA ratios, standardizing research proto-cols, and long-term evaluation in strictly selected clinical populations.